Odpowiedzi

Najlepsza Odpowiedź!
2010-01-04T21:39:52+01:00
X-jedna liczba
x+2-druga liczba
(x+2)⁴-x⁴=(x+2)²(x+2)²-x⁴=(x²+4x+4)(x²+4x+4)-x⁴=x⁴+4x³+4x²+4x³+16x²+16x+4x²+16x+16-x⁴=8x³+24x²+32x+16=8(x³+3x²+4x+2) Jest to liczba podzielna przez 8, co miałem udowodnić :)
1 5 1
  • Roma
  • Community Manager
2010-01-04T21:43:24+01:00
A, a+2 - liczby całkowite
(a+2)⁴ - a⁴ = ((a+2)²)² - a⁴ = (a² + 4a + 4)² - a⁴ = (a² + 4a + 4)*(a² + 4a + 4) - a⁴ = a⁴ + 4a³ + 4a² + 4a³ + 16a² + 16a + 4a² + 16a + 16 - a⁴ = 8a³ + 24a² + 32a + 16 = 8 * (a³ + 3a² + 4a + 2)

8 * (a³ + 3a² + 4a + 2) : 8 = a³ + 3a² + 4a + 2 ∈ C, czyli (a+2)⁴ - a⁴ jest podzielne przez 8
1 5 1